Evaluation ethics for best practice cases and commentaries - Morris, Michael 1949- (Guilford Press, 2008)
Focusing on ethical challenges in program evaluation, this innovative book features six case-study scenarios that end at a point where the evaluator faces a significant decision about how to proceed. For each case, two distinguished evaluators offer insights on the best course of action to choose, and why. "What if?" boxes modify the details of the scenarios, inviting readers to reflect on whether these changes alter the ethical implications of the case. Six additional cases are presented with questions that guide students to develop their own ethical analyses. Organized to follow the progress of an evaluation, from the entry/contracting phase through the utilization of results, this class-tested book will enhance any student or practitioner's understanding and practice of evaluation.